Recurrent stroke risk in intracranial atherosclerotic disease - Ballout, Ahmad A.; Liebeskind, David S. (Frontiers in Neurology, 2022)
Recurrent stroke risk secondary to intracranial atherosclerotic disease remains high despite aggressive medical treatment. This risk is further amplified in subgroups possessing biomarkers of hemodynamic insufficiency and potential for embolization, which have been shown to be independently and synergistically predictive of recurrent stroke. Luminal stenosis was predominantly used as entry criteria in major treatment trials, discounting the potential role of hemodynamics from primary analyses, limiting the strength of evidence and conclusions of these biomarkers to post-hoc analyses and other natural history studies. Future treatment trials should consider stratifying patients using a combination of these high-risk biomarkers. In the absence of trials, risk stratifying patients based on the presence of these markers may lend to more individualized clinical decisions. We aimed to summarize the studies that have investigated the relationship between biomarkers and their role in predicting recurrent stroke risk in intracranial atherosclerotic disease.